Female poverty and intrahousehold inequality in transition economies - Luca Piccoli (IZA World of Labor, 2017)
Transition to a market economy is accompanied by a period of greater economic uncertainty. Women are likely to suffer substantial disadvantages from this uncertainty compared to men as they are, for example, more likely to lose their job. This not only implies a monetary loss for the entire family, but also degrades female bargaining power within the household, possibly further aggravating their well-being. When intra-household inequality—an unequal distribution of resources among family members—exists, female poverty might be significantly larger than what can be deduced using standard household based poverty measures.
Keywords: D13; H31; I32; O15; 330; female poverty; intrahousehold inequality; gender gaps; transition